Representation of Latvian Mithology in works of Hilda Vika - Celmiņa-Ķeirāne, Austra; Grūbe, Signe (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
The paper includes the study on activities of the Latvian painter and writer Hilda Vika - Eglīte (1897-1963) in the field of visual art (mostly painting) connected with Latvian mythology. Latvian myth characters and themes came into H. Vika’s creative work after 1930 when she married writer and reviewer Viktors Eglitis and resorted to “Dievturība” (Latvian Neopagan religious movement based on folklore, old folk songs and mythology). Actively and productively working H. Vika participated in numerous group art exhibitions. Her individual vision, decorative solutions of composition and stylized details brought in Latvian painting unusual and essentially different intonations being contemporary at the same time. The research is pointing out H. Vika’s artworks published in various sources with identifiable mythological scenes and motifs and analysing the principles of creating visual images of characters and potential impact. Memories and reviews of contemporaries, art historians and critics are used as additional material. Latvian “Dievs” (the God in the pre-Christian religion of Balts) in painter's works is indefinable age man with light-colored (possibly gray) hair and long pale coat, the image is often surrounded by a bright halo or supplement ethnographic characters. Laima’s and Mara’s ambivalence, which lies in the folk songs where these Latvian deities operate in both - positive (cradle hanging, fertility promotion) as well as harmful or fatal aspects, in H. Vika’s paintings is completely disappeared. Laima only appears as a bright image bearing blessing alongside with Dievs and Mara. H. Vika’s Mara is depicted as the goddess of good fortune and patroness of all feminine duties and as a deity related to the person's birth and initiation rites. Sun and Sun's daughters are painted with light colour tones, dynamic compositional solutions and original interpretation of national folk costumes, supplemented with Latvian characters. H. Vika often minded the question of life and death, the end of human earthly life, and Latvian Velu mate (Mother of the souls / spirits) vividly symbolizes this theme in her works. In most cases, Velu mate is portrayed as a woman with a headscarf or woolen shawl, partly or completely covering her face, as a symbol of unknown and mysterious, the human encounters after the death. The artist focused on mythological themes with great interest and excitement, creating visual images corresponding to a Latvian folklore and ethnographic heritage and representing the external manner reminding Fra Angelico and Botticelli's painting or impact of Russian school and German neo-romanticism.